## Trending News

Promoted

### 1 Answer

Relevance

- mcbengtLv 79 years agoFavorite Answer
Yes, it is. One way to see it is to apply the angle addition formulas

cos(a+b) = cos(a) cos(b) - sin(a) sin(b)

sin(a+b) = sin(a) cos(b) + cos(a) sin(b)

a few times:

cos(3x) = cos(x + 2x)

= cos(x) cos(2x) - sin(x) sin(2x)

= cos(x) cos(x+x) - sin(x) sin(x+x)

= cos(x) (cos(x) cos(x) - sin(x) sin(x)) - sin(x) (sin(x) cos(x) + cos(x) sin(x))

= (cos(x))^3 - cos(x) (sin(x))^2 - 2 (sin(x))^2 cos(x)

... then use the fact that (sin(x))^2 = 1 - (cos(x))^2 ...

= (cos(x))^3 - cos(x) (1 - (cos(x))^2) - 2 (1 - (cos(x))^2) cos(x)

= (cos(x))^3 - cos(x) + (cos(x))^3 - 2 cos(x) + 2 (cos(x))^3

= 4 (cos(x))^3 - 3 cos(x)

Like any trig identity there are other derivations also but that is one of them.

Still have questions? Get your answers by asking now.